A guide to community foundations in Germany. - Küstermann, Burkhard; Rummel, Miriam; Schwärzel, Mirko (My University, 2016)
The Country Guide presents community foundations in Germany. Twenty years after the first community foundation was established in Germany, there is great interest abroad in German community foundations. How do community foundations position themselves within their social context? What are their legal bases? What are their distinguishing features? What is the success story that can be carried on? "A Guide to Community Foundations in Germany" examines all these questions. Further studies on the community foundation systems in European countries will follow shortly.
Keywords: Partizipation; Stiftung; Verband; Statistik; Beispielsammlung; Gemeinwohl; Ehrenamt; Bürgerstiftung; Bürgerengagement; Freiwilligkeit; Gremienarbeit